Molecular characterisation of an attenuated GdhA - derivative of Pasteurella multocida B:2 - Muhammad Azam, Farahani (2019)
Pasteurella multocida B:2 is an important veterinary pathogen causing fatal and acute Haemorrhagic septicaemia (HS) in bovine. The pathogen is usually commensal that resides in the submandibular region of buffaloes or cattle. Monsoon season is the outbreak season for the disease to commonly develop due to the weakening immunity of the animals. Endemic countries, particularly Asia, routinely administer oil-adjuvant or whole-killed vaccines for disease prevention. However, these vaccines were observed to provide short-term protection with inadequate vaccination coverage which led to a significant failure of the vaccination program. The live-attenuated vaccine was proposed to overcome the limitations provided by the current vaccines. A live vaccine candidate, P. multocida B:2 GDH7 was reported to enable protection in cattle and buffaloes via intranasal (i.n.) administration. This potential vaccine was also reported to be self-transmitted from the vaccinated animal to the freeranging animal allowing wider vaccination coverage. Prior to commercialisation, this potential vaccine requires further characterisation in accordance with the authoritative guidelines from the World Organisation for Animal Health (OIE). Hence, in this study, the potential vaccine strain, P. multocida B:2 GDH7 and the virulent parent strain will be characterised through genomic and proteomic profiling. A crucial first step was to develop a sensitive identification test to differentiate both strains which has been achieved by the development of a precise yet straightforward PCR method. In genomic profiling, Repetitive Extragenic Palindromic sequence-PCR (REPPCR) was manipulated and has demonstrated different genomic DNA band patterns of both strains. By using several bioinformatics tools, 105 outer membrane proteins (OMPs) were determined from the proteome of the parent strain. About 5-10% of the OMPs determined were observed in SDS-PAGE analysis of both strains. Some of the major OMPs especially OmpA and OmpH, are known as prominent immunogens of P. multocida, were observed to be expressed differently between the strains. In conclusion, a reproducible PCR detection method has been developed to differentiate both strains. Further characterisation of these strains shows a significantly different profile through genomic and proteomic profiling. Bioinformatics analysis had enabled selection of four antigens for future HS vaccine development.